Characterization and quantifi cation of endogenous fatty acid nitroalkene metabolites in human urine - Salvatore, Sonia Rosana (2013)
The oxidation and nitration of unsaturated fatty acids transforms cell membrane and lipoprotein constituents into mediators that regulate signal transduction. The formation of 9-NO2-octadeca-9,11-dienoic acid and 12-NO2-octadeca- 9,11-dienoic acid stems from peroxynitrite- and myeloperoxidase-derived nitrogen dioxide reactions as well as secondary to nitrite disproportionation under the acidic conditions of digestion. Broad anti-inflammatory and tissue-protective responses are mediated by nitro-fatty acids. It is now shown that electrophilic fatty acid nitroalkenes are present in the urine of healthy human volunteers (9.9 + 4.0 pmol/mg creatinine); along with electrophilic 16- and 14-carbon nitroalkenyl β-oxidation metabolites. High resolution mass determinations and co-elution with isotopically-labeled metabolites support renal excretion of cysteine-nitroalkene conjugates. These products of Michael addition are in equilibrium with the free nitroalkene pool in urine and are displaced by thiol reaction with HgCl2. This reaction increases the level of free nitroalkene fraction >10-fold and displays a KD of 7.5x10-6 M. In aggregate, the data indicates that formation of Michael adducts by electrophilic fatty acids is favored under biological conditions and that reversal of these addition reactions is critical for detecting both parent nitroalkenes and their metabolites. The measurement of this class of mediators can constitute a sensitive non-invasive index of metabolic and inflammatory status.